Faktor Geografis dan Konsepsi Peran Nasional sebagai Sumber Politik Luar Negeri Indonesia - Haryanto, Agus (Universitas Muhammadiyah Yogyakarta, 2015)
This paper discusses the geographical factor as the source of the national role conception and foreign policy of a country. Indonesia has realized his strategic geographic location that laid between two oceans and two continents since the early days of independence. Indonesia is also aware of the geographical features as an archipelagic state. Its raises awareness of Indonesia to keep his territory for the declaration of Djuanda. This paper explore the Indonesian foreign policy that still using geographical factor as a source of foreign policy. This can be seen from the efforts of Indonesia continues to participate in various regional issues that could potentially interfere the sovereignty of Indonesia such as the disputed South China Sea and East China Sea. Indonesia also seeks active in border diplomacy to ensure the sovereignty of its territory.